Do buprenorphine doses and ratios matter in medication assisted treatment adherence? - Kevin Kavanagh, PharmD, BCPP; Kimberly Tallian, PharmD, APh, BCPP; Joe A. Sepulveda, MD, FAPA, FASAM; Sarah Rojas, MD; Shedrick Martin, PharmD, BCPP; Harminder Sikand, PharmD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Buprenorphine (BUP), generally prescribed as buprenorphine/naloxone, is a key component of medication-assisted treatment (MAT) to manage opioid use disorder. Studies suggest higher doses of BUP increase treatment adherence. Routine urine drug screens (UDS) assist in monitoring MAT adherence via measurement of excreted BUP and its metabolite, norbuprenorphine (NBP). The clinical significance between BUP/NBP concentrations and their ratios for assessing adherence and substance use is not well-described. Methods: We conducted a single-center, retrospective chart review of 195 clients age ≥18 years enrolled in a local MAT program from August 2017 to February 2021. Demographics, BUP doses, prescription history, and UDS results were collected. Participants were divided based on MAT adherence (<80% vs ≥80%) and median total daily dose (TDD) of BUP (≥16 mg vs <16 mg) in addition to pre- and post-COVID-19 cohorts. Results: Median BUP/NBP urinary concentrations were significantly correlated with MAT adherence (P < .0001 for each) and a reduced percentage of positive UDS for opioids (P = .0004 and P < .0001, respectively) but not their ratios. Median TDD of BUP ≥16 mg (n = 126) vs <16 mg (n = 68) was not correlated with MAT adherence (P = .107) or incidence of nonprescription use (P = .117). A significantly higher incidence of UDS positive for opiates (P = .049) and alcohol (P = .035) was observed post-COVID-19. Discussion: Clients appearing adherent to MAT who had higher concentrations of urinary BUP/NBP demonstrated a reduced incidence of opioid-positive UDS independent of the BUP dose prescribed. An increase in opioid- and alcohol-positive UDSs were observed during the COVID-19 pandemic.